MEMAHAMI KEKERASAN KOLEKTIF SUPORTER SEPAKBOLA (Arena, 2010)
Abstract This paper aims to study about the factors that cause riots football match. Riots accompanied by collective violence, which carried Persebaya’s supporters have often occurred at the expense of many parties. Riots when playing Persebaya versus Arema on the Copa Cup to review the case of this paper. Findings of the factors triggering rioting football match is based on theoretical studies, observation, dept interview with the actor riots and forum discussion groups with relevant parties such as the Officials of East Java Province PSSI, Offcials of Persebaya, the Police and Supporters Group. From the empirical studies based on the facts supported the field and theoretical analysis, it can be concluded that the phenomenon of violence is not single threaded, but is multidimensional. Socio-economic conditions, the organization, and individual match is triggering variables.    Keyword: football, findings